2011
DOI: 10.4314/evj.v15i2.67692
|View full text |Cite
|
Sign up to set email alerts
|

Study on the seroprevalence of small ruminant brucellosis in and around Bahir Dar, North West Ethiopia

Abstract: A cross sectional study was carried out from October 2008 to April 2009 to determine the sero-prevalence of brucellosis in small ruminants in and around Bahir Dar, northwest Ethiopia. The sampling method used was purposive sampling technique for districts and simple random for the study animals. A total of 500 serum samples (270 from sheep and 230 from goats) were collected from extensive management system with no history of vaccination. All serum samples were initially screened by Rose-Bengal-Plate Test (RBPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 5 publications
4
11
7
Order By: Relevance
“…The result of the present study (3.57%) is in accordance with the findings of Ashenafi et al [10]. In contrast, lower seroprevalence [15][16][17][18][19][20][21] have been reported previously. Higher seroprevalences have also been reported previously from pastoral areas of Eastern Ethiopia (Afar, Somali and Dire Dawa regions) [9,22].…”
Section: Discussionsupporting
confidence: 93%
“…The result of the present study (3.57%) is in accordance with the findings of Ashenafi et al [10]. In contrast, lower seroprevalence [15][16][17][18][19][20][21] have been reported previously. Higher seroprevalences have also been reported previously from pastoral areas of Eastern Ethiopia (Afar, Somali and Dire Dawa regions) [9,22].…”
Section: Discussionsupporting
confidence: 93%
“…The seroprevalence obtained in the present study was higher than the report of Tekelye and Kasali (1990) who reported prevalence rates of 1.5% in sheep and 1.3% in goats in Central Ethiopia; and Ferede et al (2011) who reported prevalence proportions of 0.87% in goats and 0% in sheep in and around Bahir Dar. The report of Ashenafi et al (2007) with prevalence rate of 5.8% in goats and 3.2% in sheep in pastoral regions of Afar and that of Ashagre et al (2011) with prevalence of 4.2% in goats in South Omo zone showed fair agreement with this finding.…”
Section: Discussioncontrasting
confidence: 89%
“…In Ethiopia, few studies have been published so far on small ruminant brucellosis (Tekelye and Kasali, 1990;Teshale et al 2006;Ashenafi et al, 2007;Ferede et al, 2011;Bekele et al, 2011;Yohannes et al, 2013). Particularly, there is no published data on small ruminant brucellosis in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the overall sero-prevalence of small ruminants in this study was relatively higher than 0% in sheep and 0.5% in goats Brucellosis sero-prevalence by Ferede et al [27] in and around Bahirdar and0.5% in sheep and 0.87% in goats by Amenu et al [28] in Arsi Negele district. On the contrary, it is lower than 4.6% and 9.7% of Brucellosis prevalence from other parts of the country by Deddefo et al [29] and Teshale et al [23] respectively.…”
Section: Discussioncontrasting
confidence: 52%